A study of high-dose lenalidomide induction and low-dose lenalidomide maintenance therapy for patients with hypomethylating agent refractory myelodysplastic syndrome. Issue 11 (1st November 2016) - Cherian, Mathew A.; Tibes, Raoul; Gao, Feng; Fletcher, Theresa; Fiala, Mark; Uy, Geoffrey L.; Westervelt, Peter; Jacoby, Meagan A.; Cashen, Amanda F.; Stockerl-Goldstein, Keith; DiPersio, John F.; Vij, Ravi
Abstract: Myelodysplastic syndromes (MDS) are clonal hematopoietic disorders characterized by bone marrow failure which frequently progress to acute myeloid leukemia. Patients who fail to respond to, or progress on first-line DNA hypomethylating agents (HMA) have a poor prognosis. Conventionally dosed lenalidomide has activity in 5q-MDS. In other subtypes, it may reduce RBC transfusion requirements but does not result in cytogenetic responses. We previously reported that high-dose lenalidomide induction (50 mg/day) results in complete remissions in a high fraction of patients. We, therefore, conducted a Phase 2 trial of the same regimen in MDS refractory to HMA. Marrow complete remissions were seen in 33% of patients and hematological improvement in 8% of patients. Significant infections complicated more than 50% of cases. Future trials to explore alternative dosing schedules of high-dose lenalidomide to increase efficacy while decreasing toxicity are warranted.